2015
DOI: 10.1088/0957-0233/26/11/115203
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive force sensor based on two identical fiber Bragg gratings

Abstract: A highly sensitive force sensor is fabricated with two identical fiber Bragg gratings (FBGs). When the reflected C-band light from one FBG with axial tensile force enters another identical FBG, two close peaks will appear in the transmission spectrum of the latter. The power difference of the two peaks can be modulated by the axial tensile force. In theory, the process of producing two peaks is simulated, the relationship between axial tensile force and the wavelength of the FBG reflection-peak is analyzed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…1(b) which is an alternative to other fibre optic force sensors reported until now, see for example [7,[18][19][20][21][22][23]. The modes that participate in the interference are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1(b) which is an alternative to other fibre optic force sensors reported until now, see for example [7,[18][19][20][21][22][23]. The modes that participate in the interference are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mo et al reported a miniature and magnetic-resonance-compatible optical Fabry-Perot (F-P) force sensor [ 8 ], achieving a force sensing range of 0–5 N with a resolution of 0.1 N. Noh et al developed a three-axis fiber-optic body force sensor structure for flexible manipulators with a measurement range of 0–21 N, being suitable for inclusion in instruments and robotic tools for minimally invasive surgery [ 9 ]. Tang et al reported a sensitive force sensor using two identical fiber Bragg gratings (FBGs), achieving a sensitivity of (1.16 ± 0.06) × 10 3 dB/N [ 10 ]. Zychowicz presented a fiber-optic force sensor, operating in the configuration of a birefringent fiber based on a Sagnac interferometer, with a measurement range of 0–2 N [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strategies of controlling the membrane morphology and structure by introducing additives were reported in detail by many researches through the thermodynamic phase diagram or kinetic light transmission of phase separation [1][2][3]. Among which, polyethylene glycol (PEG) and LiCl are the common additives used as organic compound and inorganic salt respectively for membrane preparation.…”
Section: Introductionmentioning
confidence: 99%